A Legal Analysis of the Establishment and Regulatory Framework of the Merah Putih Village Cooperative in Indonesia Under Law Number 25 of 1992 on Cooperatives - Giawa, Yustina; Sihotang, Januari (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The Merah Putih Village Cooperative (KDMP) is a flagship program of the Indonesian government formulated through Presidential Instruction Number 9 of 2025 concerning the Acceleration of Establishing Merah Putih Village/Urban Cooperatives. The presence of cooperatives is highly important for improving the welfare of Indonesian communities. This program has strategic objectives to strengthen village economies, provide business resources in every village/urban ward, enhance financial inclusion, and empower local communities. This study analyzes the legal regulatory aspects and their influence on the establishment of KDMP, identifies the challenges, and examines the regulatory framework governing the capital structure, supervision, and legal obstacles in the implementation of Merah Putih Cooperatives. The analysis shows that legal regulations provide a strong framework for the establishment and management of KDMP. Proper legal aspects serve as a vital foundation for the Merah Putih Village Cooperative. This research was conducted using a normative juridical approach through the study of regulations, government documents, and recent legal sources.